Ambientes pré-convectivos em situações de escoamento de norte-noroeste em baixos níveis sobre o Rio Grande do Sul - Oliveira, Mauricio Ilha de (2015)
A climatological and synoptic evaluation of the atmospheric environments prone to severe weather under N-NW low-level flow over Rio Grande do Sul (RS) State is conducted. Atmospheric profiles from 00Z, 06Z, 12Z and 18Z were calculated using Reanalysis data for two geographically distinct regions of the state: the Serra Gaúcha (SG) and the Campanha Gaúcha (CG). Several convective parameters were calculated to identify the atmospheric ingredients useful to severe storm forecasting, which are: conditional instability, moisture availability and Vertical Wind Shear (VWS). To verify the occurrence of convective storms during, or up to 6 hours the low-level N-NW flow events, cold cloud tops were identified using images from GOES 10 and 12 satellites, associating each event with a brightness temperature category. The seasonal, annual and the distribution of the parameters as a function of depth of the convective activity is based on a quantile analysis. The parameter space between conditional instability and VWS is also investigated. The synoptic environments in which the storms develop across RS were analyzed by using mean and anomaly mean composite patterns of the relevant meteorological fields for convective weather forecasting. The climatology showed that the differences between the large-scale environments favorable to the development of storms in SG and CG are small. The expected seasonal behavior of conditional instability and VWS was well represented in this climatology. The transitional seasons are those which present both conditions of high instability and VWS and also record more storms in this regime. The analysis of the mean composites fields highlights the lack of pronounced Lapse Rates in pre-convective environments in RS. The pressure fall induced by a mid-level trough accelerates the N-NW flow which assumes a low-level jet character, responsible for increasing the supply of heat, moisture and low-level VWS. The deeper storms stand out from the others because they develop in environments with enhaced moisture and conditional instability anomalies.